2014
DOI: 10.1007/s00109-014-1167-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduced levels of maternal progesterone during pregnancy increase the risk for allergic airway diseases in females only

Abstract: Observational as well as experimental studies support that prenatal challenges seemed to be associated with an increased risk for allergic airway diseases in the offspring. However, insights into biomarkers involved in mediating this risk are largely elusive. We here aimed to test the association between endogenous and exogenous factors documented in pregnant women, including psychosocial, endocrine, and life style parameters, and the risk for allergic airway diseases in the children later in life. We further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Despite sex-specificity in immune responses is frequently reported, 33 Surprisingly, similar effects of steroid hormones were observed in T cells isolated from non-pregnant and pregnant mice early (gd 7.5) and late (gd 18.5) of gestation. We used 10 −6 M of progesterone for in vitro cultures, which represents approximately three times the serum concentration in pregnant mice at gd 16.5-the peak of progesterone concentrations in the serum.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Despite sex-specificity in immune responses is frequently reported, 33 Surprisingly, similar effects of steroid hormones were observed in T cells isolated from non-pregnant and pregnant mice early (gd 7.5) and late (gd 18.5) of gestation. We used 10 −6 M of progesterone for in vitro cultures, which represents approximately three times the serum concentration in pregnant mice at gd 16.5-the peak of progesterone concentrations in the serum.…”
Section: Discussionmentioning
confidence: 71%
“…Since sex-specific immune responses are well-known, [32][33][34][35] we next assessed whether cells derived from male and female animals are differentially affected by steroid hormones. We isolated spleen cells from male and female C57BL/6 wild-type mice and cultured them with hormones as described before.…”
Section: Progesterone-mediated T-cell Death Induction Is Also Obsermentioning
confidence: 99%
“…Bidirectional interactions between the HPA and the hypothalamic-pituitary-gonadal (HPG) axes during development may also contribute to sex differences in early life stress exposures(70, 71). Notably, a recent study in a pregnancy cohort (n=409) found a relationship between lower prenatal maternal progesterone levels early in pregnancy and increased cumulative incidence of asthma and allergic rhinitis at 3–5 years of age among girls but not among boys(72). The authors conceptualized reduced progesterone as a surrogate marker of stress, given known interactions between the HPA and HPG axes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, sex differences in the placental response to stress has been well-documented by others, and these differences are proposed to play an important role in sexually dimorphic programming of development (6,43). The sex-differences in the placental response to stress are thought to contribute the increased risk for adverse neurodevelopmental programming in males (45), and others have proposed that sex-differences in the placental response to progesterone levels might affect programming of asthma in offspring (46). The interaction of sexually dimorphic organ development with sex differences in placental functions will likely need to be considered in future studies in order to define the mechanisms underlying sex-specific developmental programming.…”
Section: Discussionmentioning
confidence: 97%